Langerhans cell histiocytosis (histiocytosis x) – in the mandible - Camargo, Angela Jordão; Cheade, Mayara; Martinelli, Celso; Monteiro, Solange Aparecida Caldeira; Santos, Christiano de Oliveira; Watanabe, Plauto Christopher Aranha (Brazilian Dental Science, 2013)
This article reports a case of 65 year-old man consultedin a private radiology dental clinic for a panoramicradiography, where was indicated a radiolucent area,extending into the periapical region of the teeth 35 to 43 to the base of the mandible. Radiographydiagnosis was difficult. The immunohistochemical examination showed immunoreactivity for theproteins CD 68, S-100 and CD 1a. Histopathologicaldiagnosis was obtained for Langerhans cell granuloma(histiocytosis X). Langerhans cell histiocytosis iscaused by the abnormal proliferation of histiocytes, previously called Histiocytosis X. It is a rare diseasethat preferentially affects children and young adultswith a predilection for males and can affect differentparts of the body. Keywords Adult; Histiocytosis; Langerhans; Mandible.